SEG Technical Program Expanded Abstracts 2004 2004
DOI: 10.1190/1.1851133
|View full text |Cite
|
Sign up to set email alerts
|

Spatial orientation and distribution of reservoir fractures from scattered seismic energy

Abstract: We present the details of a new method for determining the reflection and scattering characteristics of seismic energy from subsurface fractured formations. The method is based upon observations we have made from 3D finite difference modeling of the reflected and scattered seismic energy over discrete systems of vertical fractures.Regularly spaced, discrete vertical fractures impart a ringing coda type signature to any seismic energy which is transmitted through or reflected off of them. This signature varies … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
79
1
1

Year Published

2005
2005
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 55 publications
(85 citation statements)
references
References 10 publications
4
79
1
1
Order By: Relevance
“…Estimates of the aggregated fracture orientations using these volumes from the analysis of scattering indices are shown as rose plots in Figure 8, modified from Willis et al (2004). The rose plots, which estimate the distribution of fractures in the area around well 4 (left) and well 8 (right), agree with the ENE and NNW directions derived in the studies mentioned above and shown in Figure 7.…”
Section: Emilio Field Data Studysupporting
confidence: 69%
See 4 more Smart Citations
“…Estimates of the aggregated fracture orientations using these volumes from the analysis of scattering indices are shown as rose plots in Figure 8, modified from Willis et al (2004). The rose plots, which estimate the distribution of fractures in the area around well 4 (left) and well 8 (right), agree with the ENE and NNW directions derived in the studies mentioned above and shown in Figure 7.…”
Section: Emilio Field Data Studysupporting
confidence: 69%
“…The scattering indices were sorted and directions for those with the highest angular contrast in values (in this case for scattering index values greater than 5) were plotted as 'quivers' (i.e., short line segments) giving a map view of the location and direction of possible fractures determined by this method (Figure 20). These plots were also shown in previous reports and papers (e.g., Willis et al, 2003Willis et al, , 2004. The locations of these fracture measurements, however, are taken from stacked data (rather than migrated data), and as such, their locations are in the un-migrated positions.…”
Section: A Data Set 1: Emilio Fieldmentioning
confidence: 78%
See 3 more Smart Citations